2014
DOI: 10.1179/1743278214y.0000000232
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of graphene oxide/epoxy nanocomposite as corrosion resistance coating on carbon steel

Abstract: Graphene and its derivatives are new materials with unique properties. In recent years, various studies about the nanocomposites based on graphene oxide (GO) have been carried out. However, the electrochemical properties of nanocomposite coatings based on GO materials have not been widely studied. In this study, GO/epoxy nanocomposite coatings were prepared by incorporation of different amounts of GO nanosheets into the epoxy matrix via mechanical agitation and sonication process. The dispersion of GO nanoshee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(36 citation statements)
references
References 26 publications
0
35
0
1
Order By: Relevance
“…Cured epoxy resin has characteristic spectral bands as shown in Figure 2c, where the FTIR spectra for pure bio-epoxy resin has a broad absorption peak at 3397 cm −1 which coincides with the presence of O-H stretching of hydroxyl groups reported in this range between (3650-3000 cm −1 ) [30]. The band at 3050 cm −1 is attributed to the C-H stretching vibration of epoxy [31], while 1607, 1580 and 1508 cm −1 are related to the benzene ring of epoxy [32]. The absorption bands at 1248 cm −1 and 935 cm −1 are the symmetric stretching band of the epoxy ring [31] and the C-O band of the epoxy group [33], respectively.…”
Section: Ftir Analysismentioning
confidence: 59%
“…Cured epoxy resin has characteristic spectral bands as shown in Figure 2c, where the FTIR spectra for pure bio-epoxy resin has a broad absorption peak at 3397 cm −1 which coincides with the presence of O-H stretching of hydroxyl groups reported in this range between (3650-3000 cm −1 ) [30]. The band at 3050 cm −1 is attributed to the C-H stretching vibration of epoxy [31], while 1607, 1580 and 1508 cm −1 are related to the benzene ring of epoxy [32]. The absorption bands at 1248 cm −1 and 935 cm −1 are the symmetric stretching band of the epoxy ring [31] and the C-O band of the epoxy group [33], respectively.…”
Section: Ftir Analysismentioning
confidence: 59%
“…On the other hand, the simple mechanical dispersion of unmodified singlelayered GO in epoxy resin required vigorous mechanical mixing and intense sonication processes in order to effectively deagglomerate the GO sheets. [235] The structural and chemical modification of graphene and graphene-based materials is among the most commonly used approaches to stabilize suspensions of such material in complex environments without agglomeration taking place. Surface functionalization can play an important role in achieving good interfacial bonding between graphene sheets and the surrounding matrices.…”
Section: Dispersion In Polymeric Matricesmentioning
confidence: 99%
“…Graphene, as a two‐dimensional sheet of carbon, has being widely studied across a number of areas due to its exceptional micromechanical and thermal properties . Recently, considerable amount of papers have reported that the graphene/polymer composite possesses enhanced barrier properties that are beneficial for high anticorrosion performances . Unlike carbon nanotubes that can only provide similar mechanical benefits, these lightweight sheets can reduce oxygen permeability of host membranes .…”
Section: Introductionmentioning
confidence: 99%